Document Image Binarization Using Retinex and Global Thresholding - Wagdy, Marian; Faye, Ibrahima; Rohaya, Dayang (ELCVIA Electronic Letters on Computer Vision and Image Analysis, 2015)
Document images are usually degraded in the course of photocopying, faxing, printing, or scanning. Degradation problems seems negligible to human eyes but can be responsible for an abrupt decline in accuracy by the current generation of optical character recognition (OCR) systems. In this paper we present binarization method based on retinex theory followed by a global threshold. High quality results in terms of visual criteria and OCR performance is produced compared to the previous works.